2016
DOI: 10.1007/s11664-016-4744-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of In2S3 Layer Thickness, Band Gap and Doping Density for Effective Performance of a CIGS Solar Cell Using SCAPS

Abstract: The effect of indium sulfide buffer layer's geometrical and electro-optical properties on the Copper-Indium-Gallium-diSelenide solar cell performance using numerical simulation is investigated. The numerical simulation software used is a solar cell capacitance simulator in (SCAPS). The innermost impacts of buffer layer thickness, band gap, and doping density on the cells output parameters such as open circuit voltage, short circuit current density, fill factor, and the efficiency were extensively simulated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…So the low FF may arise because a large barrier exists at the In 2 S 3 /Zn(O,S) interface [35]. The electron affinity (χ e ) of In 2 S 3 is calculated according to Equation (3) [36]:…”
Section: The Reason For the Efficiency Limitation Of Devicesmentioning
confidence: 99%
“…So the low FF may arise because a large barrier exists at the In 2 S 3 /Zn(O,S) interface [35]. The electron affinity (χ e ) of In 2 S 3 is calculated according to Equation (3) [36]:…”
Section: The Reason For the Efficiency Limitation Of Devicesmentioning
confidence: 99%
“…Lambert beer law is used which is based on optical model for estimation of optical parameter [7]. In this work, AFORS-HET automat simulation software is used to simulate AZO/Si and TiO 2 /Si heterojunction solar cell and its various parameters like thickness of silicon wafer, thickness of AZO layer, thickness of TiO 2 layer, doping concentration of donors (N d ), effective conduction band density (N c ), and texturing at different angle is optimized [30]. Texturing of silicon wafer at different angle is performed to study the change in behaviour and performance of solar cell with respect to plane heterojunction solar cell [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, in both cases, the band gaps of CIGS and In 2 S 3 were xed. Two studies [30,31] explored the effect of the properties of the In 2 S 3 buffer layer on the performance of CIGS solar cells using numerical simulation, but variations in the CIGS absorber layer were not neglected in both studies. Sun et al also examined the effect of the band gap (E g ) of In 2 S 3 and the composition of interfacial layers between In 2 S 3 and CIGS on the e ciency of CIGS solar cells [32] and found that the properties of these interfacial layers exerted a substantial in uence on the performance of the CIGS device.…”
Section: Introductionmentioning
confidence: 99%